ANGGOTA TUBUH TERKHITBAH YANG BOLEH DI PANDANG MENURUT IBNU HAZM - Muhammad Alwin Abdillah, Rasyidin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2019)
To reach an ideal household (mawaddah warohmah), various preparatory efforts areneeded as early as possible to support the marriage. This preparation must have started since theintroduction process until there is a determination to get to the marriage level. Broadly speaking,preparations that must be required include a prospective husband and wife must be ready ormature physically, mentally (psychologically), socially and sexually. Khitbah in Indonesian isthe same as engagement, engagement or proposal. The word "khitbah" comes from Arabic whichis a masdar form of the word تطخ which means to propose or propose. In the Indonesian IslamicEncyclopedia explained that Khitbah means the proposal or proposal, which is the proposal of aman who wants to marry a woman, whether she is still a girl or already a widow. In this caseproposal can be done by men and women in accordance with the customs that apply to thecommunity or the environment they live. Ibn Hazm has his own minhaj (method) inunderstanding texts, that is, the Zhahiri minhaj which is very different from the school ofworship that is adopted by jumhur. In understanding a text Ibn Hazm took directly from theprovisions of the text al-Qur'an and the hadith, he only looked at what they can see from theoutside only. Not proclaiming the law, not searching for „illat, he eve n said that the text must beunderstood in its final way. Ibn Hazm argues that when preaching a man can see the whole bodyof his future wife without exception. Whether it's aurat or not.